Buy-Now-Pay-Later Adoption, Debt Stress, and Repurchase Intention among Filipinos Gen Z Consumers: The Mediating Role of Budgeting Self-Efficacy - Maricel A. Romero Maricel A. Romero (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2025)
Buy-Now-Pay-Later (BNPL) services have expanded rapidly across Southeast Asia, blending digital checkout convenience with short-term consumer credit. While BNPL is often marketed as a frictionless payment innovation, concerns about impulsive spending and debt stress have grown, particularly among Gen Z consumers whose digital shopping frequency is high and financial buffers are limited. This study examines the determinants and consequences of BNPL adoption among Filipinos Gen Z consumers, focusing on how adoption relates to repurchase intention through debt stress and budgeting self-efficacy. Building on financial behavior theory, self-efficacy perspectives, and perceived risk logic, the model treats BNPL adoption as a behavioral routine that can simultaneously increase purchase flexibility and amplify repayment anxiety. Survey data were collected from 602 Filipinos Gen Z consumers who had used BNPL at least twice during the preceding three months. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test direct effects and parallel mediation. Results indicate that perceived convenience and promotional attractiveness strengthen BNPL adoption, while perceived transparency reduces debt stress. Adoption is positively associated with repurchase intention but also increases debt stress; budgeting self-efficacy reduces the negative influence of stress and partially mediates the path from transparency to healthier outcomes. The findings clarify why BNPL can drive commerce growth while simultaneously creating consumer welfare risks. Policy and platform implications emphasize transparent fee disclosure, cooling-off design, and budgeting support features tailored to youth consumers.